Más allá de la oficina: cómo el trabajo a distancia está transformando las organizaciones - Rojas Plasencia, Karina Milagros (2024)
Remote work has raised questions among companies and employees regarding its effectiveness and development. Therefore, the objective of this research is to answer the question: What is the impact of remote work on organizations? To achieve this, a systematic investigation was carried out using the Prisma method, which allowed the identification, selection, and analysis of various articles from recognized databases such as Scopus and Web of Science. In the initial search, 54,003 articles were found, which were filtered according to various criteria, resulting in 30 final articles. The results show that remote work can have a positive impact on job satisfaction, work-life balance, productivity, and innovation. However, some negative impacts were also identified, such as increased fatigue, social isolation, and lack of communication.